Adaptive optics in spectroscopy and densely labeled-fluorescence applications - Edrei, Eitan (Opt Express, 2018)
Adaptive optics systems have been integrated in many imaging modalities in order to correct for aberrations that are introduced by samples and optical elements. Usually, the optical system has access to a guide star (i.e., a point-like structure that is smaller than the diffraction limit). This guide star can be used as a beacon for adaptive optics enhancement. In contrast, for spectroscopy and densely-labeled fluorescent samples, the signal is diffused throughout the entire beam path and is not confined to a well-defined point-like structure. Here, we show analytically and experimentally that, in these scenarios, adaptive optics systems are expected to yield significantly lower signal enhancement than when a guide star is available. We discuss adaptive optics’ performance degradation for different imaging modalities (e.g., confocal, multi-photon microscopy) and identify solutions to overcome low signal enhancements.